Comunicação, recepção e consumo: as manifestações culturais e sua influência na formação das identidades. Um estudo sobre as telenovelas Duas Caras (brasileira) e A Outra (portuguesa) - Abrão, Maria Amélia Paiva (2010)
Contemporary society, which has been called consumer society, characterized by constant and permanent changes, accelerated by advances in technology. Relations Communication / reception / consumption / identities, a feature of this season, are manifested in society as a whole. It is in this context that this research falls, with the corpus telenovelas Two Face, broadcast on TV Globo (Brazil), and The Other, broadcast by TVI (Portugal), both aired in prime time. Intraficção television advertising (product placement commercial) and mode (consumer) receiver that can be inferred from soap operas will be evaluated and compared in the field, subject to receipt of different socioeconomic levels. We believe that the material and symbolic aspects of goods are intrinsically linked: every product has a meaning assigned to it socially and a concrete face - stant the object itself has no value until it is used socially. This research will seek to understand the process of construction of meaning present in soap operas from the combination material / symbolic